THE IMPLICATION OF DEFINING REFUGEE IN INDONESIAN IMMIGRATION LEGAL SYSTEM - Anindito Rizki Wiraputra (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Indonesia as a country which did not ratify UN Convention 1951 on Status of Refugees and Protocol 1967, issued a Presidential Decree No.125/2016 on Handling Overseas Refugee in addressing the issues of foreign nation subject who intend to seek refuge by passing through Indonesian territory, generally aiming to seek refuge in Australia. These foreign nation subject introduced as “refugee” by media although the subject is unrecognized by Indonesian immigration law system. Indonesian immigration law only recognize subject as a person who enter or leave Indonesian territory by legal or illegal means. The definition of Refugee on Presidential Decree No.125/2016 is the first definition of the subject in Indonesian legal system, refers to both Refugee and Asylum Seekers in UN Convention 1951, which supposed to have different handling methods. Therefore, the implementation of Presidential Decree No.125/2016 leads to different understanding in immigration and foreign policy perspective on Refugee subject.